Financial Analysis and Crystal Ice Cube Busines - Eva Mirza Syafitri; Rino Desanto Wiwoho; Prasetyo Yekti Utomo (Jurnal Multidisiplin Madani, 2023)
The tube ice machine that has been designed by the Madiun Madiun State Polytechnic. Its  hopes to turn this program into a business incubator that can be maximized by the Madiun State Polytechnic Academic Community. In order for the implementation of the ice tube machine business to run well, it is necessary to carry out a financial analysis of the ice tube machine business at Madiun State Polytechnic. The method used in this research is qualitative data analysis conducted to determine the characteristics of the tofu company which is presented in non-financial aspects in the form of descriptive descriptions, tables, charts, or pictures to facilitate understanding. Quantitative data is used to determine the company's financial condition, such as NPV, IRR, Payback Period (PP), Net B/C Ratio, BEP, ROI. This quantitative analysis is presented in the form of a tabulation that groups and classifies the data in order to facilitate data analysis. Data processing is done with the help of calculators and Microsoft Excel computer programs. From the financial aspect, they are: (1) Net Present Value (NPV) of IDR 268,140,450 where the nominal is positive and feasible to run. (2) Internal Rate of Return (IRR) which is at a number where the value is greater than the discount factor, namely 100.76% > 10% DF, means it is feasible to run; (3) Benefit Cost Ratio (BCR) of 2.87 or more than one (> 1), and is feasible to run; (4) Payback Period (PP) which is within 1 year and 3 months